Geology and Radiometric Survey of Tagima area, Northern Part of Adamawa Massif, Northeastern Nigeria - Ahmed, H. A.; Halilu, M.; Rufai, F.A.; Saleh, M.B (IJRDO-Journal of Applied Science, 2017)
Field mapping and radiometric reconnaissance survey of Tagima and environs was carried out with the aim of producing geologic and isorad maps of the area and identifying possible extension of uranium mineralization southwards from the popular Mika deposit. Geologic study shows that the area is underlain by porphyritic granite, equigranular granite, migmatite and pegmatite. These rocks are characterized by joint and fault structures. Petrographic analysis of the porphyritic granite, equigranular granite, migmatite and pegmatite showed that the plagioclase, k-feldspars, biotite and quartz are the dominant minerals that constitute the rock units. Radiometric survey shows high radiometric values in the northwestern, northeastern and some of the southeastern parts of the area, while lower values are seen in the southern and southwestern parts. Analyses of the results shows high potentials for radioactive minerals in Mika and Jasori areas, while low potential for radioactive minerals in southern part of Tagima area. While Mika area has already been established to have uranium deposits, possible extension of radioactive minerals can be traced around Jasori and Tagima with decreasing potentials towards southern parts of the study area.